2000
DOI: 10.1002/1096-9071(200009)62:1<1::aid-jmv1>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

AIDS in an HIV-seronegative Ghanaian woman with intersubtype A/G recombinant HIV-1 infection

Abstract: A 29-year-old Ghanaian woman who developed AIDS while being HIV-antibody seronegative was investigated during a collaborative study aimed at the identification of viral causes of a HIV-seronegative AIDS syndrome in West Africa. Plasma was screened with a panel of EIA tests for antibodies to HIV and HIV-1 p24 antigen. Retroviral infection was investigated by detection of reverse transcriptase (RT) activity in plasma, viral RNA amplification and quantification, and virus isolation. Positive amplification product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Among non-B clades, HIV-1 subtype A infection was found in a persistently HIV-1-seronegative woman from Ivory Coast [7], subtype A2 virus was identified in an HIV-1-seronegative woman in Portugal [8], HIV-1 CRF01_AE (a circulating recombinant form of HIV-1 that is composed predominantly of subtype A and a unique envelope designated lineage E) was documented in 4 HIV-1-seronegative drug users in Thailand [9,10], and a rare A/G recombinant was found in an HIV-1-seronegative woman from Ghana [11]. To date, no studies, to our knowledge, have reported cases of seronegative HIV-1 subtype C infection, which is the predominant HIV-1 subtype in the worldwide epidemic.…”
Section: Hiv-1 Subtype B Infection Have Been Reported In Europe Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Among non-B clades, HIV-1 subtype A infection was found in a persistently HIV-1-seronegative woman from Ivory Coast [7], subtype A2 virus was identified in an HIV-1-seronegative woman in Portugal [8], HIV-1 CRF01_AE (a circulating recombinant form of HIV-1 that is composed predominantly of subtype A and a unique envelope designated lineage E) was documented in 4 HIV-1-seronegative drug users in Thailand [9,10], and a rare A/G recombinant was found in an HIV-1-seronegative woman from Ghana [11]. To date, no studies, to our knowledge, have reported cases of seronegative HIV-1 subtype C infection, which is the predominant HIV-1 subtype in the worldwide epidemic.…”
Section: Hiv-1 Subtype B Infection Have Been Reported In Europe Andmentioning
confidence: 99%
“…Although the exact time and source of HIV-1 subtype C infection is unknown, it is likely that infection occurred 11 year before death. Repeated tests for HIV-1 antibodies consistently yielded negative results, including rapid and regular ELISA and Western blot.…”
Section: Hiv-1 Subtype B Infection Have Been Reported In Europe Andmentioning
confidence: 99%
“…In North America and West Europe, HIV-1 subtype B is the most prevalent clade, although a rapid spreading of other variants has been highlighted in recent years (Alaeus et al, 1997a(Alaeus et al, , 1997bBarlow et al, 2001;Böni et al, 1999;Fleury et al, 2003;Holguín et al, 2000aHolguín et al, , 2000bHolguín et al, , 2002aHolguín et al, , 2002bOp de Coul et al, 2001). The diversity of HIV-1 may affect diagnostic tests (Apetrei et al, 1996;Baldrich-Rubio et al, 2001;Candotti et al, 2000), including those used for viral load measurements (Alaeus et al, 1997a(Alaeus et al, , 1997bHolguín et al, 1999;Jenny-Avital and Beatrice, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Serological tests for detecting antibodies against viruses in blood samples reduce, but do eliminate, the risk of viral transmission (13). For example, although the quantity of antibody against a virus may be low during the pre-seroconversion window period, the viral load can still be substantial (14)(15)(16)(17). A related detection problem exists from infection with immunovariant viruses and immunosilent carriage (18).…”
Section: Safety Of Blood and Water Suppliesmentioning
confidence: 99%